TRANSFORMATION OF TOURIST DESTINATION IN POEMS - I Gusti Ayu Agung Mas Triadnyani (Prosiding Seminar Nasional dan Internasional HISKI, 2020)
Research on tourist destinations in Klungkung Regency, Bali, which is included in the collection of poetry, Klungkung: Tanah Tua Tanah Cinta is important to do to see how far Indonesian poets recognize this area. What are the views of the poets in photographing the changes in Klungkung city and famous places in this area? In this paper, five poems contain ideas about the transformation of tourist destinations in Klungkung. The method used is an analytic descriptive and the theory of public space will be applied. The results obtained from this research are that the poets utilize public space in Klungkung which is undergoing transformation, namely the deserted Klungkung land, Balai Kerthagosa as the noiseless court, Goa Lawa Beach as a source of livelihood, Meriam I Selisik as a marker of collective memory, and the Tukad Unda Bridge. as a spiritual bridge.